Is shadow education the driver of East Asia's high performance on comparative learning assessments? - Jeremy Rappleye; Hikaru Komatsu (Arizona State University, 2020)
East Asian students consistently top comparative assessments of academic achievement. Yet, rather than attempting to develop more sophisticated understandings of this difference, the most common reaction is to attribute East Asian performance to longer study hours and/or the attendance at schools focused on academic skill enhancement and test preparation (i.e., juku). Herein we seek to contribute to a richer debate both by presenting new data and findings in relation to Japan, and by highlighting new analytical strategies to understand the relationship between East Asian performance and shadow education. Specifically, we highlight that comparatively high levels of achievement among Japanese students were apparent even at the level of fourth graders, even though juku attendance was low prior to this stage. This suggests that juku attendance is not the primary factor for the high academic achievement of Japanese students. The wider significance of these findings lies in countering both common portrayals of East Asian success and factually inaccurate information disseminated by organizations such as the OECD. In so doing, researchers are in better position to elaborate new, more sophisticated theories that explain East Asia's consistently world- leading academic achievement.